RESEARCH EDUCATION OF DOCTORAL STUDENTS IN THE CONTEXT OF HIGHER EDUCATION REFORMS IN KAZAKHSTAN: CASES OF TWO UNIVERSITIES - Kuchumova, Gulfiya (Graduate School of Education, 2021)
To prepare researchers who can “make important contributions to frontier research” (Bogle et al., 2010, p. 3) is a primary function of PhD education. PhD (doctoral) students grow as researchers by acquiring research competences through participation in a complex series of doctoral education practices (Cumming, 2010). While we have much to learn from previous research on how doctoral students are taught to do research, there is still limited understanding of research competences developed at the PhD level (Böttcher & Thiel, 2018), the interplay of doctoral education practices and doctoral students’ research competences, as well as how the development of research competences varies across disciplines and universities (Feldon, 2016). This study aims to explore how PhD programmes in Kazakhstan develop doctoral students’ research competences. A conceptual framework of PhD research education designed for this study is based on literature about research competences, research methods courses, supervision, research opportunities, and practice theory perspectives. The study employs a qualitative multiple case-study design and focuses on four PhD programmes belonging to two distinct disciplinary areas – Chemistry and History - at two universities in Kazakhstan. To gain a holistic picture of research education, this study uses different data sources. 26 participants – doctoral students, research methods instructors and local and international supervisors – took part in individual interviews. Document analysis complemented interview data. Findings from this study show that research competences developed in a PhD are interdisciplinary, knowledge-based, and comprise intellectual and technical research skills associated with the stages of the research process. The acquisition of these competences differs across individual doctoral students, localities, and more significantly between the disciplines. Despite the proliferation of research opportunities in PhD programmes, the acquisition of research competences remains substantially dependent on supervisors. This raises concerns over the quality of research education when supervision is highly non- directive and hands-off. The low contribution of other doctoral education practices is related to faculty members’ limited research capacity and pedagogy, low organisational quality, inadequate institutional research environment, and insufficient state support. The study argues that in contrast to externally-driven and top-down approaches, sustainable improvement of research education in Kazakhstan could be achieved by building the capacity of PhD programmes locally. This, in turn, requires a more substantial focus on educational gains and pedagogy of research education, as well as the environment it is embedded in.
Keywords: Type of access: Restricted; doctoral students; Kazakhstan; Research education